Artikel Review: Penggunaan Bahan Berbahaya dalam Produk Kosmetik Pada Produk Body Lotion Pemutih dan Efek Toksiknya - Amelia Defina Permatasari; Abigail Yemima Christie; Neza Ardelia Putri; Yola Asri Paramita; Hata Rianti Wasahua (Journal of Educational Innovation and Public Health, 2026)
Cosmetics are products used to care for and enhance the external appearance of the body. One widely used cosmetic product is Body Lotion, particularly whitening Body Lotion, which moisturizes and brightens the skin. However, body whitening cosmetics often contain hazardous substances such as mercury, hydroquinone and paraben, which remain a serious threat to public health. This study was conducted to identify the hazardous chemicals contained in whitening Body Lotion and evaluate their toxic impacts. Using a literature review, data was collected from various scientific databases such as PubMed, Google Scholar, and ScienceDirect, with publications within the last 5-10 years. The findings reveal that prolonged exposure to mercury can cause neurological damage and kidney disorders, while hydroquinone is associated with skin irritation and potential carcinogenic effects, and parabens are linked to endocrine disruption. These hazardous substances are frequently found in unregistered or illegally circulated cosmetic products. Regulatory agencies play a critical role in monitoring and enforcing cosmetic safety standards to protect consumers from potential health risks. This study is expected to broaden consumer education regarding cosmetic safety and serve as a reference for strengthening the supervision of beauty products.